Pengaruh Paket Biochar Plus Dan Azotobacter Terhadap Pertumbuhan Dan Hasil Padi Unggul Lokal Pada Tanah Podsolik Merah Kuning - Maylani Lucky; Sutarman Gafur; Saeri Sagiman (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2022)
Local selected rice is one of the potential rice types to be developed on up-land soil of West Kalimantan. Applying organic material such as biochar plus is one way to increase RYP soil fertility. To improve soil nitrogen content could be done by applying local selected azotobacter. The study is aimed to study the impact of biochar plus packages and the azotobacter on local rice growth and yield on RYP soil. The study used a split plot randomized experimental design. The main plot used azotobacter sp (B) B0 = without azotobacter, and B1 = using azotobacter. The subplot used biochar plus (A) consisted of A0 = without biochar plus, A1 = Biochar (7.5%) + Compost 5% + NPK (600kg/ha), A2 = Biochar (7.5%) + Compost 5% + NPK (300kg/ha), A3 = Biochar (7.5%) + Compost 5%, A4 = Biochar (7.5%) + NPK (300kg/ha).  There were 10 treatment combinations, each repeated 3 times. There were 3 plants in each replication so there were total 90 experimental units. Results showed that the biochar plus had a significant effects on all the variables observed, while the azotobacter had a significant effects on the number of productive tillers. The biochar package of 7.5% + compost 5% + NPK (300kg/ha) is considered to be more effective because it produced a similar results with that of highest result treatment.